2017
DOI: 10.1177/1010428317699798
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA DANCR, a prognostic indicator, promotes cell growth and tumorigenicity in gastric cancer

Abstract: Gastric cancer remains the third leading cause of cancer-related mortality worldwide, and proliferation of gastric cancer represents the major reason for its poor prognosis. Recent evidence indicates that long non-coding RNAs play crucial roles in development and progression of gastric cancer. Long non-coding RNA differentiation antagonizing non-protein coding RNA is upregulated in hepatic cell carcinoma, but the role of lncRNA differentiation antagonizing non-protein coding RNA in gastric cancer has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 22 publications
2
51
0
Order By: Relevance
“…The high expression of DANCR has been linked with tumor progression and poor prognosis in colorectal cancer (Liu et al, 2015), hepatocellular carcinoma (Ma et al, 2016), and gastric cancer (Hao et al, 2017).…”
Section: Dancr Expression Is Elevated In Human Aml Cells Treated Withmentioning
confidence: 99%
“…The high expression of DANCR has been linked with tumor progression and poor prognosis in colorectal cancer (Liu et al, 2015), hepatocellular carcinoma (Ma et al, 2016), and gastric cancer (Hao et al, 2017).…”
Section: Dancr Expression Is Elevated In Human Aml Cells Treated Withmentioning
confidence: 99%
“…SNHG12 could sponge MIR‐199a/b‐5p and MIR320 to promote tumorigenesis . DANCR and SNHG14 were also upregulated in gastric cancer and could promote cancer cell proliferation, invasion and migration . Mao et al described that DANCR could also regulate another lncRNA.…”
Section: Biological Functions and Mechanisms Of Snhgs In Digestive Camentioning
confidence: 99%
“…73,74 DANCR and SNHG14 were also upregulated in gastric cancer and could promote cancer cell proliferation, invasion and migration. [75][76][77] Mao et al described that DANCR could also regulate another lncRNA. They found DANCR inhibited the expression of NPTN-IT1 by binding with EZH2 and HDAC3.…”
Section: Snhgs In Gastric Cancermentioning
confidence: 99%
“…In accordance with the exclusion and inclusion criteria, 14 studies involving 1,117 patients were enrolled into this meta-analysis. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] Characteristics of the 14 studies included in this meta-analysis are summarized in Table 1. As could be observed, the sample size in the 14 studies ranged from 34 to 135, with an average of 79.57.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…26,31 All clinical pathological parameters were dependent on the pathology. Moreover, it was found that the reference genes of lncRNA DANCR were different among these studies, which had included GAPDH, [23][24][25][26][27][29][30][31][32][33][34] b-actin, 22,35 and small nuclear RNA U6. 28 Moreover, the thresholds of high and low lncRNA DANCR expression levels, including the median and average lncRNA DANCR expression, were also different among these studies.…”
mentioning
confidence: 99%